Application of CD25 and CTLA4 gene transcription levels in early prediction of acute graft-versus-host disease - Huang, Ken; Yang, Mengxin; Zhou, Yuhang; Cao, Yaxuan; Pang, Guanxiu; Zhao, Jie; Liu, Yang; Luo, Jianming (Frontiers in Immunology, 2024)
Our study investigated the potential of peripheral blood T cell CD25, CD28, and CTLA-4 gene transcription levels as predictive biomarkers for acute graft-versus-host disease (aGVHD) following allogeneic hematopoietic stem cell transplantation (allo-HSCT). Real-time reverse transcription fluorescent quantitative PCR (RT-qPCR) analysis was conducted on day +7, +14, and +21 posttransplantation in patients undergoing allo-HSCT. Elevated levels of CD25 and CTLA-4 mRNA were found to be associated with the occurrence of aGVHD, as well as severe and gastrointestinal aGVHD. Receiver operating characteristic (ROC) curve analysis was utilized to assess the predictive value of each biomarker. Combined analysis of CD25 and CTLA-4 mRNA levels demonstrated promising predictive potential for aGVHD. Our results confirmed that the transcription levels of CD25 and CTLA4 genes could be used as early predictive biomarkers for aGVHD post-allo-HSCT.